2020
DOI: 10.21320/2500-2139-2020-13-3-260-272
|View full text |Cite
|
Sign up to set email alerts
|

Achievements and Challenges of Evidence-Based Medicine in Hematopoietic Stem Cell Transplantation: An Analysis of Single-Center and Multicenter Trials

Abstract: Randomized multicenter trials in the area of hematopoietic stem cell transplantation (HSCT) face considerable challenges, therefore, their amount is relatively small. Most clinical guidelines are based on the data of multicenter registry studies or well-controlled prospective single-center non-randomized studies. To determine the criteria of a well-controlled single-center trial the results of which can be confi rmed by a multicenter analysis, the total of 44 groups of patients from 22 cooperative studies in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…In the case of autoHCT, the opposite situation is observed: NRM remains at a low level, but the relapse incidence is reduced by achieving a better response of an underlying malignant disease before autograft [3]. The comparability of results and trends with the registry data was recently analyzed in our large study, where it was shown that the results are similar in most cases when using modern pre-and post-transplantation therapy [20].…”
Section: Discussionmentioning
confidence: 87%
“…In the case of autoHCT, the opposite situation is observed: NRM remains at a low level, but the relapse incidence is reduced by achieving a better response of an underlying malignant disease before autograft [3]. The comparability of results and trends with the registry data was recently analyzed in our large study, where it was shown that the results are similar in most cases when using modern pre-and post-transplantation therapy [20].…”
Section: Discussionmentioning
confidence: 87%